Establishment of human periodontal ligament cell lines with ALPL mutations to mimic dental aspects of hypophosphatasia - Schiffmaier, Jana; Rehling, Sofia; Marnet, Katharina; Borst, Angela; Trivanović, Drenka; Docheva, Denitsa; Jakob, Franz; Graser, Stephanie; Herrmann, Marietta; Liedtke, Daniel (Frontiers in Cell and Developmental Biology, 2025)
IntroductionBesides skeletal symptoms, dental abnormalities are a typical feature of the rare inherited disorder hypophosphatasia (HPP), which is caused by loss of function mutations in the ALPL gene (alkaline phosphatase, biomineralization associated) coding for tissue-nonspecific alkaline phosphatase (TNAP). Dental symptoms include premature loss of deciduous teeth, disturbance in dentin and cementum mineralization, and an increased risk for periodontitis. However, the underlying molecular mechanisms are not fully understood and experimental cell lines for in vitro analyses of these processes are missing.MethodsWe aimed to develop a physiologically relevant cellular model of dental origin with genetic ALPL variants to investigate the molecular consequences of TNAP deficiencies in vitro. For this purpose, we used immortalized periodontal ligament stem cells (PDL-hTERT cells) to establish five independent clonal cell lines via CRISPR/Cas9, harboring different ALPL genetic variants.ResultsDetailed investigation of their genetic properties revealed that four different genotypes were successfully established at two different positions within the ALPL gene locus. The detected variants either result in mis-splicing of ALPL mRNAs or in frameshift mutations. All determined variants implied severe consequences on TNAP function, as indicated by in silico modeling and comparison to reported human pathogenic variants. Subsequent detailed cell culture experiments demonstrated TNAP residual gene expression and altered TNAP activity in the newly established ALPLtg PDL-hTERT lines. Further assessment of cell line features showed significantly reduced cell growth, partly lower levels of intracellular ATP as well as mitochondrial function proteins. TNAP activity was furthermore investigated during in vitro osteogenic differentiation and strong suppression during this process in nearly all newly established lines was observed.DiscussionWe report the generation of a new set of immortalized ALPLtg PDL-hTERT cells for investigation of TNAP cellular function in PDL cells, which can be used in subsequent studies for deciphering molecular processes in dental cells affected by reduction of TNAP function.